2023
DOI: 10.47391/jpma.akus-09
|View full text |Cite
|
Sign up to set email alerts
|

Implication of stem cells and platelet rich plasma in otolaryngology, head and neck surgical procedures

Abstract: Human body has a set of unspecialized cells called as stem cells that have the ability to generate cells of specialized function. Volume of fractionated plasma extracted from autologous blood is termed as Platelet-rich plasma (PRP) that is rich in several growth factors. Both have shown effective results in the field of regenerative medicine. Physiologically, platelets are the first cells to concentrate at the site of tissue damage, therefore application of PRP in diverse surgical procedures enhances bone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…neuroregeneration [32,33]. Animal studies have shown that growth factors and stem cells can effectively treat anosmia and regenerate olfactory neuroepithelium, positioning PRP as a promising candidate for neuroregenerative therapies [34,35].…”
Section: Literature Research and Study Designmentioning
confidence: 99%
See 4 more Smart Citations
“…neuroregeneration [32,33]. Animal studies have shown that growth factors and stem cells can effectively treat anosmia and regenerate olfactory neuroepithelium, positioning PRP as a promising candidate for neuroregenerative therapies [34,35].…”
Section: Literature Research and Study Designmentioning
confidence: 99%
“…Therapies that target the mechanisms of chronic viral infection, dysregulated immunological responses, and microvascular dysfunction that underlie OD in Long COVID may prove advantageous [37,50]. In various clinical contexts, platelet-rich plasma (PRP), a concentrated source of autologous growth factors and cytokines produced from the patient's own blood, has demonstrated promise in promoting tissue repair and regeneration [34,41]. PRP therapy may be beneficial in the context of OD linked to Long COVID through several ways.…”
Section: Od In Long-covid-19mentioning
confidence: 99%
See 3 more Smart Citations